Plasma therapy: a novel intervention to improve age-induced decline in deudenal cell proliferation in female rat model - Asmaz, Ender Deniz; Ceylani, Taha; Genc, Aysun Inan; Sertkaya, Zeynep Tugce; Teker, Hikmet Taner (Springer Science and Business Media LLC, 2025)
Abstract Aging is associated with a disruptive decline in gastrointestinal health leading to decreased duodenal cell proliferation ultimately affecting the digestive and absorptive capacity of intestines in all species. This study investigates the novel application of blood plasma therapy to enhance duodenal cell proliferation associated with aging. In the presented study, the effects of middle aged plasma therapy on the aged rat duodenum were investigated. For this purpose, using a randomized controlled design, Female Wistar rats (aged 12–15 months) (n:7) were treated with heterologus pooled plasma (0.5 mL per day for 30 days, infused intravenously into the tail vein) collected from middle aged (6 months old, n:28) rats during all stages of the estrous cycle. The groups were divided into three as the Experimental group (aged 12–15 months) receiving middle aged plasma, the control group (aged 12–15 months) not receiving treatment, and the middle aged rat (6 months) as the positive control group. At the end of the experiment, each group’s duodenum were collected, fixed, and analyzed using histological techniques for morphometric parameters. Additionally cell proliferation density and proliferation index were determined by proliferating cell nuclear antigen (PCNA). The finding of the study suggests that plasma therapy significantly improves cell proliferation, villus height (µm), crypt depth (µm), total mucosal thickness (µm), the ratio of villus height to crypt depth (µm), and surface absorption area (mm2) in the experimental group compared to control. Likewise, we determined that middle aged plasma application supports cell proliferation. However, further research is warranted to explore the underlying mechanisms and potential clinical applications of this innovative approach.
Keywords: Aging; Plasma; Duodenum; Plasma treatment; Animals; Female; Histomorphology; Rats, Wistar; Intestinal Mucosa; Cell proliferation; Research Article; Cell Proliferation; Rats